Report Cards as a Tool for Empowering Communities in the Fight Against HIV/AIDS in Cameroon : A Work in Progress - World Bank (Washington, DC, 2012)
The use of report cards in a HIV/AIDS prevention program in Cameroon appears to be a promising tool for galvanizing community interest, discussion and action. This paper includes the following content: genesis of the report cards; the report card methodology; implementation of the report card approach; observations on the report card process; refining the report card approach; and suggestions for improving the program. The paper concludes that people seem to appreciate and to be drawn into engagement in the difficult discourse on HIV/AIDS by the innocence and even fun of the report card game. They feel a sense of power by influencing actions on HIV/AIDS and judging the quality of health and support services. It appears that this report card approach may well be internalized in the HIV/AIDS program of Cameroon in such a way that it will provide a sustainable contribution to the prevention of this disease.